PERLINDUNGAN HUKUM TERHADAP KERUGIAN KREDITUR DALAM PERJANJIAN LISAN HUTANG PIUTANG AKIBAT WANPRESTASI DENGAN PEMBUKTIAN ELEKTRONIK - Fortuna, Arina Dewi; Saputra, Arikha (UNES Law Review, 2023)
The case of debts and receivables fulfilling deaflut in the case of The Padang Court Decision Number 153/Pdt.G/2020/Pn Pdg was caused by the negligence of the debtor which caused the creditor to suffer losses. To obtain its rights, the creditor must prove the existence of the agreement. However, such contracts are only oral in nature and therefore have weak legal force. To prove the debtor’s negligence, creditors use electronic evidence in the form of screenshoot of Whatsapp messages and proof of transfers. Electronic evidence submitted is considered valid evidence under UU No.19 tahun 2016 tentang ITE. This research case is normative legal research and the research method is descriptive analysis. Analysis of The Padang Court Decision Number 153/Pdt.G/2020/Pn Pdg. The results of research on the decision concluded that the legal protection of oppression was given after a dispute arose or was resolved. In this case the creditor filed a lawsuit with The Padang Distric Court to get the fairest settlement. According to creditors to seek legal protection for bankrupt debtors in court when the plaintiff appears to have bad intentions and is evasive. Until the final decision, the plantiff and the defendant must fulfill their obligations under the agreement.